Mechanical and curing properties of crumb rubber irradiated in polar media filled the tire tread blend - Alshukri, Adnan A.; Abdul Aziz, Faieza; Salit, Mohd Sapuan; Zageer, Dheaa S.; Abdul Aziz, Nuraini; Al-Maamori, Mohammed H. (American Scientific Publishers, 2017)
The problem of disposal of the waste tire has become a serious global issue as it has affected economy and ecology of nations. As such, recycling provided a powerful solution for the increasing number of worn out tires dumped into the landfills. In order to enhance the properties and activity of creating a new bond with the polymer matrix, crumb rubber (CR) from the whole tire is irradiated while being immersed in different polarity media such as air, toluene, glacial acetic acid and trichloroacetic acid. The resulting irradiated materials are incorporated into the virgin rubber, in amount according to the tire tread recipe, to investigate the effects of irradiation on the mechanical and morphological characteristics of the resulting rubber composites. The results revealed that CR irradiated in high polarity media such as Acetic acid (ACOH) and Trichloroacetic acid (TCA) show better tensile and elongation properties, while CR irradiated with Trichloroacetic acid (TCA) indicated the best abrasion resistance. The finding from the rheological study has shown enhancement in the curing characteristics especially that concerns curing time and viscosity for all the blends filled with irradiated CR in various media types. Findings also revealed that the index of curing rate was high for the CR irradiated in high polarity media such as ACOH and TCA. In comparison by weight of the content of CR in the tire tread blend, there are indications that the content can be doubled by using the new irradiated CR.